Rick Steves' Europe. 10 new shows 2011-2012 [videorecording (DVD)] - Steves, Rick, 1955- (Backdoor Productions, 2010)
This two-disc DVD includes the new Rick Steves' Europe public television programs. Included are ten half-hour episodes, ranging from Estonia to Bosnia to Morocco, along with a one-hour special on Spain's Andalucia. Featured shows: Andalucia: The Best of Southern Spain; Croatia: Adriatic Delights; Dubrovnik and Balkan Side-Trips; The Best of Slovenia; Granada, Cordoba and Spain's Costa del Sol; Andalucia, Gibraltar, and Tangier; Norway's West: Fjords, Mountains and Bergen; Stockholm; Helsinki and Tallinn: Baltic Sisters; Northern Spain and the Camino de Santiago.